Local extensional flows promote long-range fiber alignment in 3D collagen hydrogels. (1st July 2022) - Ahmed, Adeel; Mansouri, Mehran; Joshi, Indranil M; Byerley, Ann M; Day, Steven W; Gaborski, Thomas R; Abhyankar, Vinay V
Abstract: Randomly oriented type I collagen (COL1) fibers in the extracellular matrix are reorganized by biophysical forces into aligned domains extending several millimeters and with varying degrees of fiber alignment. These aligned fibers can transmit traction forces, guide tumor cell migration, facilitate angiogenesis, and influence tissue morphogenesis. To create aligned COL1 domains in microfluidic cell culture models, shear flows have been used to align thin COL1 matrices (<50 µ m in height) in a microchannel. However, there has been limited investigation into the role of shear flows in aligning 3D hydrogels (>130 µ m). Here, we show that pure shear flows do not induce fiber alignment in 3D atelo COL1 hydrogels, but the simple addition of local extensional flow promotes alignment that is maintained across several millimeters, with a degree of alignment directly related to the extensional strain rate. We further advance experimental capabilities by addressing the practical challenge of accessing a 3D hydrogel formed within a microchannel by introducing a magnetically coupled modular platform that can be released to expose the microengineered hydrogel. We demonstrate the platform's capability to pattern cells and fabricate multi-layered COL1 matrices using layer-by-layer fabrication and specialized modules. Our approach provides an easy-to-use fabrication method to achieve advanced hydrogel microengineering capabilities that combine fiber alignment with biofabrication capabilities.